SAFETY INCIDENTS CLASSIFIED AS CLINICAL PROCESS/PROCEDURE IN HOSPITALIZED PATIENTS DURING THE COVID-19 PANDEMIC - Hermann, Ana Paula; Medeiros, Adeli Regina Prizybicien de; Jesus, Elizabete da Silva Dantas de; Brandão, Marilise Borges; Santos, Nathalia Telles Paschoal; Wolff, Lilian Daisy Gonçalves (Cogitare Enfermagem, 2023)
Objective: Compare reported patient safety incidents related to a clinical process/procedure among patients with laboratory-confirmed COVID-19 diagnosis and with Severe Acute Respiratory Syndrome (SARS) caused by another infectious or undetermined agent and the other patients. Results and discussion: retrospective, documentary study approved by the ethics committee in a public teaching hospital in southern Brazil. In the study, 2,191 notifications and records of COVID-19 between March and September 2020 were used. The data were submitted to descriptive analysis with frequencies of the variables in the data set, Fisher's test to determine the associations between outcomes (classification/process/problem) and calculation of relative risk to measure its strength. The incidence of pressure ulcers was almost 3.7 times higher in patients with SARS. In the others, various tube-related incidents and events associated to the surgical process predominated. Conclusion: Intensive nursing care for patients with SARS, risk management and strengthening of good practices for the safety of all patients were relevant.